Staying young while growing old — The Munich region as everyday space of its future senior residents? - Kramer, Caroline; Pfaffenbach, Carmella (Raumforschung und Raumordnung | Spatial Research and Planning, 2007)
The article starts from the assumption that the current generation of 50-plus, due to differences in structural conditions and biographical background, differs considerably from today's senior citizens in terms of capabilities and expectations. This circumstance is discussed with regard to its consequences for the development of the Munich metropolitan area. Based on qualitative interviews, the current living conditions, future conceptions of life, and visions of aging of this cohort are presented. The conclusion is drawn that these future senior citizens represent increasing demand for inexpensive housing, while having little need for infrastructure designed to suit the special needs of the elderly in the near future. In the case of this cohort, demand for such facilities will set in at a much later point in time. However, whenever the need does arise, a larger group will have to be accommodated.